1984
DOI: 10.1002/j.1460-2075.1984.tb02188.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]ethylpropylamiloride, a radio-labelled diuretic for the analysis of the Na+/H+ exchange system. Its use with kidney cell membranes.

Abstract: The interaction of amiloride and several amiloride derivatives with the Na+/H+ exchange system in Madin‐Darby canine kidney cells and in rabbit renal microvillus membrane vesicles was studied from 22Na+ uptake experiments. On both types of preparation, the order of potency of the different molecules tested is: ethylisopropylamiloride greater than ethylpropylamiloride (EPA) greater than amiloride greater than benzamil. 3H‐labelled EPA was prepared and used to titrate amiloride binding sites in solubilized micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Other factors, including parathyroidectomy, glucocorticoid administration, unilateral nephrectomy, potassium depletion, and renal ablation also increase the V.,. of the brush border Na+/H+ antiporter (1,(5)(6)(7)(8). Recently a sodium/bicarbonate cotransporter has been described in basolateral membrane vesicles prepared from rabbit renal cortex (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors, including parathyroidectomy, glucocorticoid administration, unilateral nephrectomy, potassium depletion, and renal ablation also increase the V.,. of the brush border Na+/H+ antiporter (1,(5)(6)(7)(8). Recently a sodium/bicarbonate cotransporter has been described in basolateral membrane vesicles prepared from rabbit renal cortex (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the involvement of the Na+-H+ antiport in the regulation of the outward transport of newly-formed dopamine is, however, circumstantial and stands mainly on the fact that amiloride and EIPA are well-known inhibitors of the Na+-H+ antiport, EIPA being far more potent than amiloride (Vigne et al, 1984). This and the finding that EIPA was more potent than amiloride in reducing the outflow of dopamine strongly suggests that inhibition of the Na+-H+ antiport affects the cell outward transport of dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present work was to evaluate the role of the Na+-H+ exchanger on the renal outward transport of dopamine; the results described here are on the effects of inhibitors (amiloride and EIPA; Vigne et al, 1984) and activators (quinoxaline and phenylephrine; Nord et al, 1987;Gesek & Schoolwerth, 1989; of the Na+-H+ exchanger on the outflow of dopamine in rat kidney slices loaded with L-DOPA. A preliminary account of some these findings has been presented previously (Soares-da-Silva, 1992b (Sokal & Rolhf, 1981 Figure 1, this effect was significantly more marked for EIPA than for amiloride; the ICm value for EIPA was 5.6 ± 0.3 l.M.…”
Section: Introductionmentioning
confidence: 99%
“…10 presents the time course of "Rb' uptake by C6 cells that had been incubated under different conditions of intracellular pH (pHi) and of osmolarity of the incubation media. First, under iso-osmotic conditions, the rate of ouabain-insensitive "Rb' uptake was measured in the absence or the presence of 0.1 mM ethylisopropylamiloride, a potent inhibitor of the Na+/H+ exchange system [13,27,28]. Previous experiments have shown that the pHi of C6 cells was 1.35 and 7.0 in the absence and the presence of ethylisopropylamiloride respectively [I 31.…”
Section: Intracellulur P H Had No Influence On the Activitymentioning
confidence: 99%